Effectiveness of a locally produced ready‐to‐use supplementary food in preventing growth faltering for children under 2 years in Cambodia: a cluster randomised controlled trial. Issue 1 (29th December 2019) - Borg, Bindi; Sok, Daream; Mihrshahi, Seema; Griffin, Mark; Chamnan, Chhoun; Berger, Jacques; Laillou, Arnaud; Roos, Nanna; Wieringa, Frank T.
Abstract: This cluster randomised controlled trial tested the effectiveness of a locally produced, fish‐based, ready‐to‐use supplementary food (RUSF) to prevent growth faltering (decline in z‐scores). Cambodian infants (n= 485), aged 6 to 11 months, were randomised by site to receive the RUSF, Corn‐Soy Blend++ (CSB++), micronutrient powders (MNP), or no supplement (control). The intervention was for 6 months. In unadjusted analysis, the control group had statistically significantly decreased weight‐for‐age z‐scores (WAZ; ‐0.02, 95%CI = ‐0.03 ‐ ‐0.01, P = 0.001) and height‐for‐age z‐scores (HAZ; ‐0.07, 95%CI = ‐0.09 ‐ ‐0.05, P < 0.001), and increased mid‐upper arm‐circumference (MUAC; 0.02cm, 95%CI = 0.01 ‐ 0.04, P = 0.010), but no statistically significant change in weight‐for‐height z‐scores (WHZ). The RUSF group did not differ significantly from the control for WAZ, HAZ or WHZ (in other words, WAZ and HAZ decreased and WHZ did not change), but had increased MUAC in comparison to the control (0.04cm, 95%CI = 0.01 ‐ 0.06, P = 0.008). There were no statistically significant differences between the RUSF group and the CSB++ or MNP groups with respect to WAZ, HAZ, WHZ or MUAC. Interestingly, in adjusted analysis, low consumers of RUSF had increased WAZ, WHZ and MUAC (0.03, 95%CI = 0.01‐0.06, P = 0.006; 0.04, 95%CI = 0.01‐0.08, P = 0.026; and 0.05cm, 95%CI = 0.02‐0.09, P = 0.004, respectively) compared with the control. The novel RUSF, particularly in small quantities, protected against ponderal growth faltering, but the improvements were of limited clinical significance.